(untitled) (Research, Society and Development, 2023)
Peripartum dilated cardiomyopathy (PPCM) is a form of heart failure of unidentifiable origin, which represents an important cause of non-obstetric maternal mortality in the world, occurring in the last month of pregnancy or months after delivery, abortion or miscarriage. Compared to other forms of cardiomyopathy, PPCM promotes greater formation of intracardiac and systemic thrombi, which is why the administration of anticoagulant therapy is recommended as a strategy for the prevention of deleterious events. The present study aims to evaluate anticoagulant therapy in PPCM. For this Scope Review, carried out through the PubMed and ScienceDirect platforms, between 2018 and 2023, the chosen descriptors were ’’Anticoagulants’’, ’’Dilated Cardiomyopathy’’ and ’’Peripartum Period’’. Inclusion criteria consisted of 1) clinical trials, controlled and randomized tests, reviews and meta-analyses, 2) studies on anticoagulation in PPCM, 3) texts that addressed the management of patients with anticoagulated PPCM 4) articles written in Portuguese , English or Spanish. Exclusion criteria included thematic inadequacies, case reports, animal studies and texts outside the time frame. The evidence found suggested that the main risks of anticoagulation in PPCM are stroke, maternal hemorrhage and retroplacental bleeding. Systemic arterial hypertension, structural arrhythmias and cardiogenic shock are considered frequent complications associated with PPCM. Clinical analyzes about toxicity and better strategies for suspending anticoagulants should be developed, as well as the use of markers in the screening of PPCM.